Evaluation of the Effectiveness of Nordic Walking Training in Improving the Gait of Persons with Down Syndrome - Skiba, Agnieszka (Biomed Res Int, 2019)
People with Down syndrome (DS) show dysfunction of gait, expressed by disturbed character of angular changes and values of the spatiotemporal parameters as compared to the physiological norm. It is known that exercises and various activities have positive effect on balance and gait, but there are only a few scientific proofs concerning above-mentioned in people with DS. Furthermore, the effect of Nordic Walking (NW) training on gait in people with DS is unexplored. We enrolled 22 subjects with DS, aged 25-40 years, with moderate intellectual disability. Participants were randomly divided into 2 groups: NW training group which underwent 10 weeks of training at a frequency of 3 times a week and control group with no specific intervention. Subjects were examined twice: 1 week before training and a week immediately after intervention. Gait was evaluated by the Vicon 250: a computerized system of three-dimensional analysis of motion, connected to 5 infrared video cameras. We conducted mixed-design ANOVA model to assess the effects of time and type of training on spatiotemporal parameters. We found significant favorable time by group interaction in the following parameters: step length in right leg: F(1,15) =14,47, p=0.002; left leg accordingly F(1,15) =5,15, p=0.038, cycle length in right leg: F(1,15) =14,48, p=0.002; left leg accordingly F(1,15) =15,09, p=0.001; and gait standardised speed F(1,15) =5,35, p=0.035. Statistically significant changes were observed in numerous kinematic parameters of ankle, knee, pelvis, and shoulder in NW group. Regular NW training has positive influence on selected spatiotemporal and kinematic parameters in people with Down Syndrome and may be an attractive and safe form of rehabilitation.